1988
DOI: 10.1002/art.1780310502
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fasting on disease activity, neutrophil function, fatty acid composition, and leukotriene biosynthesis in patients with rheumatoid arthritis

Abstract: Fourteen patients with rheumatoid arthritis (RA) were studied before, during, and after a 1-week total fast. Disease activity decreased, as did the neutrophil release of lysozyme induced by the ionophore A23187. The ability of zymosan-activated RA patient serum to aggregate control neutrophils was reduced, together with serum concentrations of C3. The relative contents of arachidonic acid and eicosapentaenoic acid were increased in serum, platelets, and neutrophils, whereas levels of linoleic acid and linole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(58 citation statements)
references
References 49 publications
4
53
0
1
Order By: Relevance
“…We analyzed samples from 2 experiments in which subjects had fasted for 2 or 7 days, respectively 23,24 ; and found that PCSK9 levels were reduced by 70% to 80% ( Figure 3A and 3D). In parallel, serum lathosterol levels were reduced by 50% to 60% ( Figure 3B and 3E), again showing a parallel regulation with PCSK9.…”
Section: Fasting But Not a Ketogenic Diet Suppresses Pcsk9 Serum Lementioning
confidence: 99%
See 1 more Smart Citation
“…We analyzed samples from 2 experiments in which subjects had fasted for 2 or 7 days, respectively 23,24 ; and found that PCSK9 levels were reduced by 70% to 80% ( Figure 3A and 3D). In parallel, serum lathosterol levels were reduced by 50% to 60% ( Figure 3B and 3E), again showing a parallel regulation with PCSK9.…”
Section: Fasting But Not a Ketogenic Diet Suppresses Pcsk9 Serum Lementioning
confidence: 99%
“…23 Fasting for 7 days (starvation) ( Figure 3D-3F) was studied in samples from a previous study, 24 in which 5 women with rheumatoid arthritis underwent evaluation for effects on disease activity.…”
Section: Subjects and Study Designmentioning
confidence: 99%
“…These subjects, relative to those on an "ordinary" diet throughout the trial, experienced significant improvement in the number of swollen and tender joints, pain score, duration of morning stiffness, grip strength, ESR, and scores on the Health Assessment Questionnaire. Theories about the mechanism of improvement with fasting have included the effects of weight loss, alterations in fecal flora, and alterations in inflammatory cell activity (20)(21)(22)(23). Kjeldsen-Kragh et a1 and Darlington and Ramsey indicated that improvements in disease activity are independent of changes in weight (15,19).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Takahashi et al (1997) reported that the serum and urine levels of the pentosidine are correlated with the RA activity and then proposed that the serum and urine pentosidine might be a significant novel marker for evaluating RA disease status. In addition, dietary regimens such as fasting, caloric restriction, or vegetarian diet have the beneficial effects by improving symptoms of patients with RA (Beri D, 1988;Hafström, 1998;Kjeldsen-Kragh J, 1991). In the present study, the urine level of pentosidine in patients was significantly higher than that of control females.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary regimens such as fasting, caloric restriction, or a vegetarian diet have the beneficial effects of improving the symptoms of patients with RA (Beri D, 1988;Forre, 1991;Hafström, 1998;KjeldsenKragh J, 1991;Sköldstam et al, 1979;Stroud, 1983;Udén et al, 1983).…”
Section: Introductionmentioning
confidence: 99%